2008
DOI: 10.1007/s00244-008-9150-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fitness of Daphnia magna Fed a Bt-Transgenic Maize Variety

Abstract: Genetically modified (GM) maize expressing the Bt-toxin Cry1Ab (Bt-maize) was tested for effects on survival, growth, and reproduction of the water flea Daphnia magna, a crustacean arthropod commonly used as a model organism in ecotoxicological studies. In three repeated experiments, D. magna were fed 100% ground maize in suspension, using either GM or isogenic unmodified (UM) maize. D. magna fed GM-maize showed a significantly reduced fitness performance: The mortality was higher, a lower proportion of female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 47 publications
0
92
1
1
Order By: Relevance
“…In contrast with these results, Bøhn et al (2008) observed an earlier onset of reproduction and reduced survival in D. magna fed MON810 Bt-maize kernels of a different hybrid, suggesting a weak adverse effect of rCry1Ab, for which the concentration was approximately 30-fold lower than in leaf feed used in this study. This apparent discrepancy seems to indicate the absence of a toxic effect of the MON810 rCry1Ab in D. magna, but one needs to bear in mind that the influence of rCry1Ab (or any other toxin) might be modulated by food quantity and quality (Heugens et al, 2006;Chandini, 1989).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast with these results, Bøhn et al (2008) observed an earlier onset of reproduction and reduced survival in D. magna fed MON810 Bt-maize kernels of a different hybrid, suggesting a weak adverse effect of rCry1Ab, for which the concentration was approximately 30-fold lower than in leaf feed used in this study. This apparent discrepancy seems to indicate the absence of a toxic effect of the MON810 rCry1Ab in D. magna, but one needs to bear in mind that the influence of rCry1Ab (or any other toxin) might be modulated by food quantity and quality (Heugens et al, 2006;Chandini, 1989).…”
Section: Discussioncontrasting
confidence: 99%
“…This includes (i) delayed reproduction and reduced clutch size and total fecundity at low toxin concentrations, with additional negative effects on body size and survival at high toxin concentrations (Villarroel et al, 2003;Heugens et al, 2006); (ii) severely impaired growth, reproduction, and survival (high toxicity); and (iii) early-life fecundity compensation at the expense of later growth and survival (low toxicity) (Bøhn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in D. magna D. magna has been used as an ecotoxicological model for testing GM crop plants in short-term studies (Mendelson et al 2003;Raybould and Vlachos 2011) and over the full life-cycle (Bøhn et al 2008), and for testing combinatorial effects of Bt toxins and predation risk (Bøhn et al 2010). Cuhra and co-workers tested chronic effects of glyphosate and Roundup and showed that environmental concentrations of 0.05-0.45 mg/l (active ingredient) cause negative effects on D. magna offspring size and reproduction (Cuhra et al 2013).…”
Section: The Daphnia Magna Modelmentioning
confidence: 99%